Data Driven Health Education for Adolescent Reproductive Readiness in Stunting Prevention at the TeFa Laboratory of PSDKU MIK Ngawi - Kurniawan Erman Wicaksono; Nesa Ayu Murthisari Putri; Titin Andriyani Atmojo; Budi Fajar Supriyanto; Waridad Umais Al Ayyubi (Universitas STRADA Indonesia, 2026)
Stunting remains a major public health issue in Ngawi Regency, where the prevalence reaches 15.3%, indicating the need for targeted early prevention, especially among adolescents who face high risks of anemia and inadequate nutritional intake. This community service program aimed to strengthen the knowledge and readiness of adolescent health cadres through data-driven reproductive health education at the Teaching Factory Laboratory of PSDKU MIK Ngawi. Using a community-based participatory design, the program involved 26 cadres from 13 villages and included health education, digital literacy training, and the use of real adolescent health data. Pre-test and post-test instruments, structured observations, interviews, and digital data tools were used to assess changes in knowledge related to reproductive health, anemia, nutrition, and stunting prevention. The results showed a substantial improvement, with cadres in the good category increasing from 19% to 85% after the intervention. The average knowledge score rose from 62.31 to 83.85, and the Wilcoxon test produced a p-value below 0.001, indicating significant improvement. The biggest increase occurred in understanding the relationship between anemia and stunting, which improved by 42%, followed by better skills in interpreting adolescent health indicators for early detection. These findings demonstrate that integrating real health data with structured educational activities enhances cadres’ comprehension, promotes evidence-based decision making, and strengthens their capacity to identify adolescents at risk. Overall, the program highlights the effectiveness of data-driven health education in supporting long-term stunting prevention efforts at the community level.